Experimental study on co-pyrolysis characteristics of typical medical waste compositions - Deng, Na; Cui, Wen-qian; Wang, Wei-wei; Zhang, Qiang; Zhang, Yu-feng; Ma, Hong-ting (Journal of Central South University, 2014)
Thermal decomposition of 21 kinds of binary mixtures between typical medical compositions was investigated under nitrogen conditions by dynamic thermogravimetric analysis (TGA) at 25–800 °C. The weighed sum method (WSM) coupled with thermal analysis was applied to study the interaction between components. Then, co-pyrolysis kinetic model of the binary mixtures (tube for transfusion (TFT) and gauze) was established to verify the reliability of conclusions. The results show the follows. 1) Strong or weak interactions are shown between binary mixtures containing polyvinyl chloride (PVC), the main ingredient of TFT. The addition of other medical waste could enhance first stage decomposition of TFT. While, the secondary stage pyrolysis may be suppressed or enhanced or not affected by the addition. 2) There exists no interaction between catheter and other component, the DTG peak temperature representing CaCO 3 decomposition in catheter fraction is obviously lower than that of pure catheter; while, the shape of DTG peak keeps unchanged. 3) No evident reaction occurs between the other mix-samples, it is considered that their co-pyrolysis characteristics are linear superposition of mono-component pyrolysis characteristics.